Reconstruction of Masculinity Through Instagram @lakilakibaru: Rekonstruksi Maskulinitas Melalui Instagram @lakilakibaru - Nurul Aziza; Poppy Febriana (Academia Open, 2023)
General background: Masculinity is traditionally shaped by social and cultural norms, often promoting dominance and assertiveness. Specific background: Aliansi Laki-Laki Baru (@lakilakibaru) on Instagram challenges these norms by promoting a more inclusive form of masculinity. Knowledge gap: There is limited research on how digital platforms, like Instagram, influence the reconstruction of masculinity. Aims: This study explores how new masculinity is constructed through the @lakilakibaru account. Results: A netnographic analysis of 23 Instagram posts from 2019 to 2021 reveals four key aspects: ethnicity, education, religion & beliefs, and status & lifestyle, promoting positive behavior, knowledge, principles, and family involvement. Novelty: The study offers new insights into how social media reshapes traditional masculine roles. Implications: It emphasizes the potential of digital platforms in fostering inclusive gender identities. Highlights: Aliansi Laki-Laki Baru promotes a new masculinity that counters traditional gender norms. Key aspects of new masculinity include ethnicity, education, religion & beliefs, and lifestyle. Social media plays a crucial role in reshaping and reconstructing masculinity in a positive way. Keywords: Masculinity, Instagram, Aliansi @lakilakibaru, Gender Roles, Netnography